Сlinical case of a blast plasmocytoid dendritic cell tumor - E. N. Milikhina; T. V. Chermnykh; S. V. Koshkin; O. D. Maximov (State Scientific Center of Dermatovenereology and Cosmetology, 2019)
The reason for writing this article was the difficulty in the differential diagnosis of skin lesions in a patient of 40 years, with a preliminary diagnosis of T-cell lymphoma. During the examination, including histological, immunomorphological, immunohistochemical methods, markers of various cell lines (T, B, myeloid) were detected. This feature is characteristic of lymphomas from plasmacytoid dendritic cells (MAC), a new nosological unit. In the WHO classification (2001), tumors with a similar phenotype were included in the lymphoma section of natural killer cells (NK-blast lymphomas). The clinical case described by us illustrates the need for an integrated approach in the diagnosis of lymphomas, which makes it possible to promptly assign adequate therapy.